Image Impulse Noise Reduction Using a Conjugate Gradient of Alternative Parameter (European Journal of Pure and Applied Mathematics, 2023)
Conjugate gradient approaches emphasise the conjugate formula. This study creates a new conjugate coefficient for the conjugate gradient approach to restore pictures using Perry’s conjugacy condition and a quadratic model. Algorithms have global convergence and descent. The new technique performed better in numerical testing. The new conjugate gradient technique outperforms the FR method. The new technique performed better in numerical testing. The new conjugate gradient technique outperforms the FR method.
Keywords: Alternative Parameter gradient; Global convergence; Image restoration problems